2016
DOI: 10.1016/j.dental.2016.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Influence of nanogel additive hydrophilicity on dental adhesive mechanical performance and dentin bonding

Abstract: Objective To assess the influence of hydrophilicity of reactive nanogels on the mechanical performance of dental adhesives and microtensile bond strength (μTBS) to dentin after 24 h or 3 months of aging. Methods A series of three nanogels were synthesized: NG1—IBMA/UDMA; NG2—HEMA/BisGMA; NG3—HEMA/TE-EGDMA. The nanogels were dispersed in solvent, HEMA or BisGMA/HEMA. The degree of conversion (DC) of the materials was measured and the flexural modulus of these polymers was evaluated in dry or wet conditions. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 35 publications
0
9
0
1
Order By: Relevance
“…It also provides significantly higher bond strength to dentin and stable mechanical properties (flexural modulus and flexural strength) up to 7 days water‐storage 53 . However, the level of hydrophilicity of the nanogel affects not only its mechanical performance but also dentin bond strength and stability of the restorative material over time, but improved results have been reported when nanogels developed with an amphiphilic behavior were investigated 144 …”
Section: Discussionmentioning
confidence: 99%
“…It also provides significantly higher bond strength to dentin and stable mechanical properties (flexural modulus and flexural strength) up to 7 days water‐storage 53 . However, the level of hydrophilicity of the nanogel affects not only its mechanical performance but also dentin bond strength and stability of the restorative material over time, but improved results have been reported when nanogels developed with an amphiphilic behavior were investigated 144 …”
Section: Discussionmentioning
confidence: 99%
“…Gotti et al 92 formulated the effect of hydrophobicity on the mechanical property of dental adhesive. Three different nanogel was employed in this study.…”
Section: Physical Chemical and Mechanical Characterization Of Dental ...mentioning
confidence: 99%
“…The clinical manifestation of these factors are materials with short service lives (5.7 years) 16 , higher incidences of secondary caries and higher oral health-care costs 17 . In addition, the utilization of hydrophilic monomers in dental adhesives has been shown to adversely affect the water sorption and solubility properties of these types of dental biomaterials 18 21 , and to result in the attainment of a semi-permeable hybrid layer susceptible to slow processes of hydrolytic degradation. Such high permeability facilitates the absorption of water (via diffusion 9 and capillarity 20 ), promotes the formation of water trees (a 3-dimensional network of interconnecting pores), and results in polymeric matrixes that are expanded and plasticized, and the leaching of unreacted hydrophilic monomers (such as TEGDMA, HEMA, bis-GMA, UDMA, etc.).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that titanium dioxide nanoparticles (n-TiO 2 ) may be successfully incorporated into commercially available polymer compositions as a promising strategy to improve the properties (antibacterial and bioactivity) of dental adhesive resins 18,27 . These metaloxide nanoparticles display excellent mechanical properties (high elastic modulus and hardness), are hydrolysis resistant, cost-effective and are capable of producing reactive oxygen species (ROS) when irradiated with UV.…”
mentioning
confidence: 99%